Nigeria: The impact of COVID-19 and food system responses - COVID-19 Hub (International Food Policy Research Institute, 2021)
As Nigeria continues to face the effects of the COVID-19 pandemic, CGIAR and partners have expanded access to quality seeds and improved crop varieties, strengthened capacity of women and youth, and informed national responses and policies with evidence-based recommendations.